Response surface methodology applied to Supercritical Fluid Extraction (SFE) of carotenoids from Persimmon (Diospyros kaki L.). (1st October 2016) - Zaghdoudi, Khalil; Framboisier, Xavier; Frochot, Céline; Vanderesse, Régis; Barth, Danielle; Kalthoum-Cherif, Jamila; Blanchard, Fabrice; Guiavarc'h, Yann
Highlights: Xanthophylls and carotenes were extracted from persimmon fruit. Supercritical Fluid Extraction (SFE) with CO2 was used as extraction method. A response surface methodology (RSM) was used for modeling and optimization. Xanthophylls were better extracted in 30 min at 300 bars, 60 °C, 3 mL/min CO2 flow. β-carotene was better extracted in 30 min at 100 bars, 40 °C, 1 mL/min CO2 flow. Abstract: Supercritical carbon dioxide with ethanol as co-solvent was used to extract carotenoids from persimmon fruits ( Diospyros kaki L.). Based on a response surface methodology (RSM), a predicting model describing the effects of CO2 temperature, pressure, flow rate, ethanol percentage and extraction time was set up for each of the four carotenoids of interest. The best extraction yields in our experimental domain were found at 300 bars, 60 °C, 25% (w/w) ethanol, 3 mL/min flow rate and 30 min for xanthophylls (all- trans -lutein, all- trans -zeaxanthin and all- trans -β-cryptoxanthin). The yields were 15.46 ± 0.56, 16.81 ± 1.74 and 33.23 ± 2.91 μg/g of persimmon powder for all- trans -lutein, all- trans -zeaxanthin and all- trans -β-cryptoxanthin, respectively. As a non-oxygenated carotenoid, all- trans -β-carotene was better extracted using 100 bars, 40 °C, 25% (w/w) ethanol, 1 mL/min flow rate and 30 min extraction time, with an extraction yield of 11.19 ± 0.47 μg/g of persimmon powder.